From Neuroscience to Law: Bridging the Gap - Pernu, Tuomas K.; Elzein, Nadine (Frontiers in Psychology, 2020)
Since our moral and legal judgements are focused on our decisions and actions, one would expect information about the neural underpinnings of human decision-making and action-production to have a significant bearing on those judgements. However, despite the wealth of neuroscientific data, and the public attention it has attracted in the past few decades, the results of neuroscientific research have had relatively little influence on legal practice. It is here argued that this is due, at least partly, to the discussion on the relationship of the neurosciences and law mixing up a number of separate issues that have different relevance on our moral and legal judgements. The approach here is hierarchical; more and less feasible ways in which neuroscientific data could inform such judgements are separated from each other. The neurosciences and other physical views on human behaviour and decision-making do have the potential to have an impact on our legal reasoning. However, this happens in various different ways, and too often appeal to any neural data is assumed to be automatically relevant to shaping our moral and legal judgements. Our physicalist intuitions easily favour neural-level explanations to mental-level ones. But even if you were to subscribe to some reductionist variant of physicalism, it would not follow that all neural data should be automatically relevant to our moral and legal reasoning. However, the neurosciences can give us indirect evidence for reductive physicalism, which can then lead us to challenge the very idea of free will. Such a development can, ultimately, also have repercussions on law and legal practice.